Assessing the Open Source Development Processes Using OMM. (4th October 2012) - Petrinja, Etiel; Succi, Giancarlo
Abstract : The assessment of development practices in Free Libre Open Source Software (FLOSS) projects can contribute to the improvement of the development process by identifying poor practices and providing a list of necessary practices. Available assessment methods (e.g., Capability Maturity Model Integration (CMMI)) do not address sufficiently FLOSS-specific aspects (e.g., geographically distributed development, importance of the contributions, reputation of the project, etc.). We present a FLOSS-focused, CMMI-like assessment/improvement model: the QualiPSo Open Source Maturity Model (OMM). OMM focuses on the development process. This makes it different from existing assessment models that are focused on the assessment of the product. We have assessed six FLOSS projects using OMM. Three projects were started and led by a software company, and three are developed by three different FLOSS communities. We identified poorly addressed development activities as the number of commit/bug reports, the external contributions, and the risk management. The results showed that FLOSS projects led by companies adopt standard project management approaches as product planning, design definition, and testing, that are less often addressed by community led FLOSS projects. The OMM is valuable for both the FLOSS community, by identifying critical development activities necessary to be improved, and for potential users that can better decide which product to adopt.